MODELING OF HEAT AND MASS TRANSFER PROCESS OF HUMIDIFIED AIR IN THE REGENERATIVE HEAT EXCHANGER - A. E. Aleshin; A. V. Tsygankov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Abstract. It is proved that the design and the choice of mode require to consider the possibility of condensation from the exhausting air on the cold surfaces of the heat exchangers. The paper considers the numerical method of the regenerative heat exchanger calculation, taking into account the phase transitions (evaporation, condensation). Based on the operating principle of regenerative heat exchangers is proved the need to consider the heat transfer process inside the nozzle. It is proved that the calculation of heat and mass transfer processes in the regenerative heat exchanger of the air-conditioning systems is reduced to the solution of three nonlinear differential equations with appropriate boundary conditions. In the developed model are used the equation of state of an ideal gas and convective heat and mass transfer. The algorithm to solve the nonlinear safe equations on the space-time lattice using Seidel approach is proposed.